Can the fNIRS-derived neural biomarker better discriminate mild cognitive impairment than a neuropsychological screening test? - Park, Jin-Hyuck (Frontiers in Aging Neuroscience, 2023)
Early detection of mild cognitive impairment (MCI), a pre-clinical stage of Alzheimer’s disease (AD), has been highlighted as it could be beneficial to prevent progression to AD. Although prior studies on MCI screening have been conducted, the optimized detection way remain unclear yet. Recently, the potential of biomarker for MCI has gained a lot of attention due to a relatively low discriminant power of clinical screening tools. Therefore, this study evaluated biomarkers for screening MCI by performing a verbal digit span task (VDST) using functional near-infrared spectroscopy (fNIRS) to measure signals from the prefrontal cortex (PFC) from a group of 84 healthy controls and 52 subjects with MCI. The concentration changes of oxy-hemoglobin (HbO) were explored during the task in subject groups. Findings revealed that significant reductions in HbO concentration were observed in the PFC in the MCI group. Specially, the mean of HbO (mHbO) in the left PFC showed the highest discriminant power for MCI, which was higher than that of the Korean version of Montreal Cognitive Assessment (MoCA-K) widely used as a screening tool for MCI. Furthermore, the mHbO in the PFC during the VDST was identified to be significantly correlated to the MoCA-K scores. These findings shed new light on the feasibility and superiority of fNIRS-derived neural biomarker for screening MCI.